Cortical phosphorylated [alpha]-Synuclein levels correlate with brain wave spectra in Parkinson's disease - Caviness, John N; Lue, Lih-Fen; Hentz, Joseph G; Schmitz, Christopher T; Adler, Charles H; Shill, Holly A; Sabbagh, Marwan N; Beach, Thomas G; Walker, Douglas G (Movement disorders, 2016)
Introduction Quantitative EEG features have been identified as surrogates and predictors of cognitive decline/dementia, a common feature of progressive PD. The biochemical correlates for altered quantitative EEG features are unknown. Our primary objective was to test the hypothesis that quantitative EEG measures correlate with cortical levels of phosphorylated [alpha]-synuclein, a modified form of the synaptic protein [alpha]-synuclein, in PD cases, in contrast to other pathology-associated proteins. A secondary objective was to explore the same correlations among cellular fractions of these proteins. Methods We used posterior cingulate cortex autopsy tissue from 44 PD subjects with various degrees of cognitive decline, who had undergone EEG. In this brain region, which is a major hub of the default mode network, biochemical measurements for levels of phosphorylated [alpha]-synuclein, unmodified [alpha]-synuclein, amyloid beta peptide, phosphorylated tau, and key synaptic proteins were analyzed and data correlated with spectral EEG measures. Results Findings revealed significant correlations between background rhythm peak frequency and all bandpower values (highest in delta bandpower) with total phosphorylated [alpha]-synuclein, but not any correlation with total [alpha]-synuclein, phosphorylated tau protein, amyloid beta peptide, or synaptic proteins. Certain fractions of synaptosomal-associated protein 25 showed correlation with some quantitative EEG measures. Conclusions These data show an association between increased phosphorylation of [alpha]-synuclein and the abnormal EEG signatures of cognitive decline. Results suggest that quantitative EEG may provide an in vivo approximation of phosphorylated [alpha]-synuclein in PD cortex. This adds to previous evidence that quantitative EEG measures can be considered valid biomarkers of PD cognitive decline. © 2016 International Parkinson and Movement Disorder Society